Design Strategies for High‐Energy‐Density Aqueous Zinc Batteries - Ruan, Pengchao; Liang, Shuquan; Lu, Bingan; Fan, Hong Jin; Zhou, Jiang (Angewandte Chemie International Edition, 2022)
In recent years, the increasing demand for high‐capacity and safe energy storage has focused attention on zinc batteries featuring high voltage, high capacity, or both. Despite extensive research progress, achieving high‐energy‐density zinc batteries remains challenging and requires the synergistic regulation of multiple factors including reaction mechanisms, electrodes, and electrolytes. In this Review, we comprehensively summarize the rational design strategies of high‐energy‐density zinc batteries and critically analyze the positive effects and potential issues of these strategies in optimizing the electrochemistry, cathode materials, electrolytes, and device architecture. Finally, the challenges and perspectives for the further development of high‐energy‐density zinc batteries are outlined to guide research towards new‐generation batteries for household appliances, low‐speed electric vehicles, and large‐scale energy storage systems. Safe, inexpensive aqueous zinc batteries are expected to play a vital role in the next‐generation energy storage systems, but they currently display insufficient energy density. This Review articulates the design strategies effective in boosting the capacity, voltage, or both, highlights the challenges, and finally makes suggestions for future research directions.